2017
DOI: 10.1177/1461444817724168
|View full text |Cite
|
Sign up to set email alerts
|

Online opportunities and risks for children and adolescents: The role of digital skills, age, gender and parental mediation in Brazil

Abstract: This article presents a study that applies integrated and multi-factor path analysis to report the direct and indirect effects of young Brazilian individual and home factors on their online opportunities and risks. The results show that engaging in more online opportunities, being older and having a lower level of parental mediation are associated with a higher number of online risks. At the same time, being older, having Internet access at home, having parents with a higher educational level, possessing more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0
23

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 52 publications
(99 reference statements)
3
55
0
23
Order By: Relevance
“…We similarly deepen understanding of connectivity. Previous studies have pointed to connectivity's advantages, such as the independent information seeking that students may undertake online (Zheng et al, 2016;Zucker and Light, 2009), and disadvantages, such as the distracting or risky activities that students engage in with Internet-connected computers (e.g., Cabello-Hunt et al, 2018;Tripp, 2011;Wainer et al, 2008). We find three other strong impacts of connectivity, namely, that connectivity enables or constrains teachers' access to digital resources (i.e., online educational content), teachers' practices for assigning activities that entail or do not entail Internet use, and students' resources for completing assigned activities with or without Internet.…”
Section: Discussionmentioning
confidence: 99%
“…We similarly deepen understanding of connectivity. Previous studies have pointed to connectivity's advantages, such as the independent information seeking that students may undertake online (Zheng et al, 2016;Zucker and Light, 2009), and disadvantages, such as the distracting or risky activities that students engage in with Internet-connected computers (e.g., Cabello-Hunt et al, 2018;Tripp, 2011;Wainer et al, 2008). We find three other strong impacts of connectivity, namely, that connectivity enables or constrains teachers' access to digital resources (i.e., online educational content), teachers' practices for assigning activities that entail or do not entail Internet use, and students' resources for completing assigned activities with or without Internet.…”
Section: Discussionmentioning
confidence: 99%
“…The dimension that contains the items mostly about software regulation is considered sensible not to be discussed in researches of parental mediation strategies in television usage. One of the studies regarding parental mediation strategies in internet usage was conducted in Brazil and three dimensions that are "active mediation", "co-using" and "restrictive mediation" were determined (Cabello-Hutt, Cabello & Claro, 2017). The data obtained from eight European countries revealed the dimensions of "active mediation for Internet usage", "child-initiated support", "active mediation of Internet safety", "technical controls", "parental monitoring" and "parental restriction" (Livingstone et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Making use of some technologies to restrict particular channels, programs and websites are among the methods for restriction. Monitoring is defined as to monitor the Internet activities of adolescents afterwards (Cabello-Hutt, Cabello & Claro, 2017). The Internet example is parents` habits to check the children`s ``history`` of Internet usage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, in cluster 2, research on students' use of iPad applications to obtain scientific knowledge and ask inquiries when they visited a science museum (Marty et al, 2013). Cluster 3 had a study on Brazilian students' online use and their home background (Cabello-hutt, Cabello, & Claro, 2017). On the one hand, many of the authors found in cluster 4 worked together for Taiwanese primary school students' ICT literacy improvement and learning-assistance tool (Huang et al, 2010).…”
Section: Research Papermentioning
confidence: 99%